The Role of Motivation in Moderating the Influence of Organizational Culture and Work Environment on Wahidiyah University Lecturer Performance - Sumiati, Sumiati (ProBisnis : Jurnal Manajemen, 2023)
The research objective was to determine the role of motivation in moderating the influence of organisational culture and work environment on the performance of lecturers at Wahidiyah University. The research approach uses a quantitative approach with causal techniques. The population of this study was 100 lecturers using the Slovin rule, so a sample of 80 lecturers was obtained. The research instrument used a questionnaire with a Likert scale. Data analysis in this study uses Moderated Regression Analysis (MRA), assisted by SPSS v.25 application for Windows. Based on the research results, it can be concluded that organisational culture positively influences lecturer performance with a sig value of 0.000 <0.05. The organisational culture variable, moderated by the motivational variable, further strengthens the interaction effect of the two. Furthermore, the work environment variable positively affects performance with a sig value of 0.001 <0.05, which means the work environment can improve performance. After being moderated by motivation, there is a strong relationship between the work environment and performance. This means that motivation strengthens the influence of the work environment on performance